New member of the family Niphargidae from Croatia, Niphargus radzai, sp. n. (Contribution to the Knowledge of the Amphipoda 273) - Karaman, Gordan S. (Zootaxa, 2014)
One new species of the genus Niphargus Schiödte, 1849 (Amphipoda, Gammaridea, Niphargidae) from the subterranean waters (springs) above Ravno Vrdovo in Dinara Mountain, Croatia, is described. Niphargus radzai sp. n. belongs to the artificial group within Niphargus with elevated number of setae along outer margin of dactylus in gnathopods 1 and 2 and dactylus of some or all pereopods provided with additional spines along inner margin. The differences between N. radzai and some other similar members of this group of taxa are discussed.